Effect of microstructure on stainless steel due to variable temperature using plasma cutting / Muhammad Danial Hakim Mohd Faisal - Mohd Faisal, Muhammad Danial Hakim (2022)
For this Final Year Project (FYP), the topic given is effect of microstructure on stainless steel due to variable temperature using plasma cutting. To simplify the process for this whole project is a piece of stainless will be cut using plasma cutting process. The cut part then will be bring to the lab. The surface of the cut will be examine and see using a microscope. The microstructure behaviour then will be identify and will be record. Based on the record, research about the material properties like hardness, tensile and composition for the type of microstructure seen need to be known. This process will be done using microscope, grinder and polisher machine, and hardness tester machine in the lab. The purpose of this project is to improvised the use of plasma cutting process in our industry and to determine either it is safe to use stainless steel after it has been cut using the process. If I it safe for the environment and users, then this process will have a huge impact in our manufacturing and engineering industries.